P165 Patients with systemic lupus erythematosus and lymphoma at a tertiary hospital. (23rd March 2020) - Galindo, María; Martin, Maria; García, Aimara; Montalvo, Minerva
Abstract : Background: Evidence of an increased risk to develop haematological malignancy, especially non-Hodgkin's lymphoma (NHL) in autoimmune diseases, has been gathered since the 1970s. In the last decade studies from SLE cohorts have consistently shown a markedly increased risk of NHL. Objectives: To analyze clinical and disease characteristics in SLE patients who developed a lymphoma during follow-up, as well as to define characteristics of the lymphoma and its evolution. Methods: Retrospective observational, longitudinal study conducted in a tertiary hospital. Medical records of 362 patients with ≥4 SLICC classification criteria of SLE were reviewed, including those with lymphoma diagnosis. Demographic and clinical data, comorbidities, SLE manifestations and therapy, data related to lymphoma and outcome were collected. Descriptive statistic analysis with measures of central tendency and measures of variability was performed. Results: Of the 362 SLE patients, 9 (2.5%) were diagnosed of lymphoma, of which 100% female. Mean age at SLE diagnosis was 34 y.o (SD 11) and average duration from SLE diagnosis to lymphoma was 17 years (SD 14). 7 patients were Caucasian and 2 Hispanic. Observed comorbidities were hypertension (67%), diabetes (22%), dyslipidemia (33%), HBV infection (11%) and active smoking (66%). No malignancy history was detected. Most frequent SLE features were haematological (100%), joint (56%) and skin (56%) involvement. The serious ones were: 3 patients with haemolytic anaemia (1 of them, platelets <20000), 2 epilepsia (1 with CNS vasculitis), 1 glomerulonephritis, 1 pulmonary hypertension and 1 hemophagocytic syndrome. Only 1 patient had overlap with Sjögren's syndrome. At the time of lymphoma diagnosis, 7 patients were on steroids, 4 on immunosuppressants (2 mycophenolate, 1 azathioprine, 1 rituximab) and 3 on antimalarials (table 1 ). Mean age at lymphoma diagnosis was 51 y.o (SD 10). 5 patients (56%) had diffuse large B-cell lymphoma (DLBCL); 1, NHL; 1, Hodgkin's lymphoma; 1, mantle B-cell lymphoma and; 1, MALT. Only 1 patient, of 4 with available data, had EBV positive in the tissue. 7 patients received chemotherapy and 2 patients completed treatment with autologous peripheral stem-cell transplantation. Three patients died, 2 due to lymphoma and one due to other causes (severe flaccid paralysis). Overall survival after lymphoma diagnosis was 8 years (SD 6). Conclusion: In our patients, unlike that reported in the literature, lymphoma diagnosis was in SLE with longer duration of the disease, and all cases were female. Most frequent subtype was NHL, and all patients had previous haematological manifestations. Regarding previous SLE treatments, 5 patients had been exposed to immunosuppressants.